تطبيق طريقة الاستجابة الجسدية الكاملة في تعليم اللغة العربية - Mustapa Mustapa; Anita Andriya Ningsih; Muhammad Mubasysyir Munir (UIN Maulana Malik Ibrahim Malang, 2021)
The TPR (Total Physical Response) method in its implementation through speech instructions given to learners can be played through real examples that are meaningful and understandable. The nature of this study is descriptive analysis, which is the regular parsing of data that has been obtained, then given understanding and explanation in order to be well understood by readers. So that the steps taken are 1) learners must actively listen well to what is demonstrated by the teacher with the vocabulary keywords mentioned and the commands given by the teacher with examples of the use of such vocabulary in everyday life or phenomena that are around, 2) the student's task in listening to the teacher's demonstration explanation explaining the existing vocabulary must be in some time and not just once and thoroughly, 3) The next stage is to deify and imitate, 4) the teacher tries to order students without keywords or demonstrations or other stimulus, 5) Students act or demonstrate teacher commands, 6) creative and innovative demonstrations are carried out by teachers so that students are more understanding and able to imitate well, 7) teachers give varied command models without demonstrations or demonstrations, and 8) then in the final stages students are able to protest to colleagues in turn.